Pengaruh Usaha Mikro Kecil dan Menengah (UMKM) Terhadap Perekonomian di Indonesia - Lestari, Kinanti Mugi; Dwibasha’ir Budiman, Muhammad Danang; Filardhy, Muhammad Khalifah; Zamba, Nabila; Nurhaliza, Nasywa Sania; Alfiani, Mita; Wardiah, Mia Lasmi (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2024)
Micro, small and medium-sized enterprises (MSMEs) dvelopment in Indonesia is really important with the large number of MSMEs spread throughout the country. As one of the important sectors of the economy and its large number will certainly affect economic growth and improvement. So with the contribution of the government and MSMEs actors, it is hoped that it can accelerate the level of the Indonesian economy. In this research the author aims to analyze how the role of MSMEs can influence the Indonesian economy, as well as finding out the challenges and obstacles therein. By using a qualitative approach in the form of a literature study, the research method focuses on analyzing several previous research results that are continuous with the topic discussed. The influence of MSMEs on the Indonesian economy is the object of discussion, with the scope of data used coming from journal articles, books, e-books, websites, and so on. It was concluded that MSMEs are very influential and even become the backbone of the Indonesian economy, from creating jobs to contributing to producing export products. Even though there are obstacles such as difficult access to financing, digitalization, regulations, and MSME product innovation, the government is trying to carry out financing programs such as People's Business Credit (KUR), carrying out business incubation, encouraging the use of digital technology, and providing business assistance.